Beyond the scalpel: humanistic training and professional identity formation in postgraduate plastic surgery education - Zhengbing Guo; Yang Li; Han Chen; Xing Fan (Frontiers in Medicine, 2026)
Objective Postgraduate plastic surgery education has traditionally emphasized anatomical knowledge, operative technique, aesthetic judgment, and procedural competence. However, plastic surgery practice is also shaped by aesthetic expectations, body image concerns, psychosocial vulnerability, medico-legal risk, and commercialized doctor-patient relationships. These tensions suggest that technical training alone is insufficient for preparing trainees to manage the humanistic challenges of contemporary plastic surgery. This study aimed to develop a Professional Identity Formation (PIF)-based humanistic framework for postgraduate plastic surgery education. Methods This study adopted a review and framework-development design. First, bibliometric mapping was conducted using records from the Web of Science Core Collection to identify the thematic structure of medical humanities education. Second, literature on litigation, malpractice claims, patient complaints, negative reviews, and medico-legal risks in plastic surgery was synthesized to clarify the specialty-specific conflict structure. Finally, the two evidence streams were integrated through the lens of PIF to construct a humanistic training framework for postgraduate plastic surgery education. Results The keyword co-occurrence analysis identified four major thematic clusters in medical humanities education: reflection-driven clinical learning, narrative-based patient understanding, professional identity and sustainable empathy, and contextualized whole-person care. The synthesis of plastic surgery conflict literature showed that disputes are rarely caused by technical failure alone, but are shaped by outcome-expectation gaps, complications, informed-consent and documentation problems, communication breakdowns, commercialization and professional-boundary tensions, and system-process failures. Integrating these findings, this study proposes a PIF-based humanistic framework that connects reflective learning, patient narratives, sustainable empathy, whole-person care, and professional conscience with the real clinical challenges of plastic surgery training. Conclusion Humanistic training in plastic surgery should not be treated as an optional supplement to technical education. Rather, it should be understood as a core process through which trainees develop ethical judgment, professional boundaries, emotional resilience, patient-centered responsibility, and a stable professional identity.